25. La Légende de Xenakis: Meta Xenakis - Curtis Roads (Meta-Xenakis: New Perspectives on Iannis Xenakis’s Life, Work, and Legacies, 2024)
This is a personal account of the impact Xenakis had on my life over several decades. I am not an expert on Xenakis’s life. These recollections view Xenakis through the narrow lens of my encounters with him. The story begins with his course in Formalized Music at Indiana University in 1972. This encounter was life changing. It gave me clear focus and direction, which was crucial in my university studies. The idea of using algorithmic processes in music composition attracted me from an intellectual standpoint as a formidable design problem. In 1973 I flew to Paris to attend the Festival d’Automne. The main goal of my visit to Paris was to experience Xenakis’s sound and light spectacle Polytope de Cluny in the medieval Musée de Cluny. Returning to California, I was determined to synthesize granular sound by computer. I left CalArts for the University of California, San Diego (UCSD) where they had a working computer sound synthesis system. In 1981 I visited the CEMAMu in Issy-les-Moulineaux to see a demonstration of the UPIC system by Xenakis and his assistant Cornelia Colyer. Guy Médigue, the lead engineer of the UPIC, was also present. In the summer of 1987, I had a residency as a visiting composer at the CEMAMu, working with the UPIC system. In 1993 I left IRCAM to teach at Les Ateliers UPIC in the suburb of Massy. It was in this period that I came to know personally Xenakis and his circle.